Strategi Pembelajaran Bahasa Arab di MTs Nurul Istifadah Gebangan (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study examines the Arabic language learning strategies at MTs Nurul Istifadah Gebangan, focusing on the implementation of audio-visual methods, educational games, and digital learning applications. The research employs a qualitative approach through interviews with the Principal (Sulhan Wahyudi), Vice Principal for Curriculum (Misbahus Sudur), Arabic Language Teacher (Muslihatul Ilfah), and a 10th-grade student (Budianto). The findings reveal that the audio-visual method enhances students’ comprehension and pronunciation through interactive videos, songs, and recorded conversations. Educational games, such as Arabic Scrabble and role-playing, make learning more engaging and boost students' motivation. The use of digital applications like Duolingo Arabic and Nahwu Shorof enables flexible learning both inside and outside the classroom. This study concludes that a combination of technology-based strategies and active interaction can improve students' interest and understanding of the Arabic language. As a recommendation, the school should further develop the use of AI-based media and blended learning methods to enhance learning effectiveness.